Fabella Syndrome and Common Peroneal Neuropathy following Total Knee Arthroplasty - Connor C. Diaz; Avinesh Agarwalla; Brian Forsythe (Case Reports in Orthopedics)
Case. A 62-year-old man presented with persistent lateral knee pain 15 months following an uncomplicated total knee arthroplasty. There was a tendinous snapping structure over the lateral aspect of the knee in deep flexion with positive Tinel’s sign over the fibular head. The patient underwent an uncomplicated flabella excision. The patient was cleared to return to work and full duty at two months postoperatively. Conclusion. Flabella syndrome is a rare but increasingly common mechanism of persistent lateral knee pain following total knee arthroplasty. Surgeons should be aware of this etiology of persistent lateral knee pain and offer treatment modalities to address this pathology.